Three Measures of Current Levels of Religiosity - Alston, Jon P. (Journal for the scientific study of religion, 1975)
Based on three measures of religiosity collected in a national sample, about one-fourth to one-half of the population could be considered religious. Catholics are more religious than Protestants, who are more religious than Jews, and females continue to be more religious than males.